2019
DOI: 10.1021/acs.jpcc.9b01435
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effect of Surface Strain on CO Binding to Pd Thin Films

Abstract: We report measurements to investigate the effects of mechanical strain on the binding energy of carbon monoxide (CO) on the (111) surface of a 16 nm thin film of palladium (Pd) grown on rutile titanium dioxide (r-TiO2). The lattice mismatch between Pd and the r-TiO2 leads to a tensile mechanical in-plane stress in the Pd layer of approximately 0.38 GPa. We observe an increase of (40 ± 10) kJ mol–1 in the CO binding energy for the 16 nm sample compared to a bulk Pd(111) crystal, which is in qualitative agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Therefore, the CO resistance improves in the order from NPG-Pd, NPG-PdCu, Pd/C to NPG-PdCuAu as indicated in Figure 3a. Previous literature reported that compressing the lattice of Pd could weaken the binding energy of Pd−CO and Cu could provide hydroxyl groups at low potentials to remove the surface-adsorbed CO. 10,[15][16][17]34 Integrating with the XRD patterns in Figure 2a, NPG-PdCu with a smaller lattice parameter and a higher initial Cu proportion should exhibit a better CO resistance than NPG-PdCuAu which is obviously different from the data in Figure 3a. To explore the reasons for this apparent anomaly, surface compositions of NPG-PdCu and NPG-PdCuAu electrodes were separately detected during the conventional potential cycling experiments for stable surface structures before electrochemical measurements.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…Therefore, the CO resistance improves in the order from NPG-Pd, NPG-PdCu, Pd/C to NPG-PdCuAu as indicated in Figure 3a. Previous literature reported that compressing the lattice of Pd could weaken the binding energy of Pd−CO and Cu could provide hydroxyl groups at low potentials to remove the surface-adsorbed CO. 10,[15][16][17]34 Integrating with the XRD patterns in Figure 2a, NPG-PdCu with a smaller lattice parameter and a higher initial Cu proportion should exhibit a better CO resistance than NPG-PdCuAu which is obviously different from the data in Figure 3a. To explore the reasons for this apparent anomaly, surface compositions of NPG-PdCu and NPG-PdCuAu electrodes were separately detected during the conventional potential cycling experiments for stable surface structures before electrochemical measurements.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…The apparatus used in this work is similar to that used in earlier VRK experiments. , It consists of a source chamber equipped with both a Parker Series 9 General Valve and an Even-Lavie type nozzle, producing two pulsed molecular beams. Both beams are skimmed and pass two stages of differential pumping before entering an ultrahigh vacuum chamber with a base pressure of 6 × 10 –10 mbar where a Pt(332) sample is held.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…For surface kinetics experiments, the clean and reconstructed sample is then transported in front of the molecular beam behind an ion imaging detector similar to those described previously. , Molecules leaving the surface are ionized at a distance of about 10 mm from the surface via nonresonant multiphoton ionization using 800 nm pulses from a Ti:Sa laser (120 fs, 1 kHz, 450 μJ per pulse) focused with a 150 mm plano-convex lens. The ions are generated between a repeller and an extractor grid, both with a diameter of 41 mm and separated from one another by 5 mm.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Apart from the strain that arises from the vertical misfit of Pd (111) on rutile TiO 2 (110), there is also an influence from the lateral misfit. Harding et al [39] used XRD to measure the out-of-plane lattice parameter of a 164 Å thick Pd (111) film also grown on rutile TiO 2 (110). From that, the in-plane strain and stress were computed.…”
Section: Strain Imparted On Supported Nanoparticlesmentioning
confidence: 99%
“…The study of metals supported on oxides such as TiO 2 have been extensively studied due the importance of such systems in catalysis [36,37]. Recent studies show that the TiO 2 substrate can impart strain onto the supported nanoparticles, changing their reactivity to CO molecules [38,39]. Strain can also be introduced into a material by implanting objects beneath the surface.…”
Section: Introductionmentioning
confidence: 99%